Clinical intervention for gang-involved youth: toward an empirically validated model - Boxer, Paul (The Oxford handbook of gangs and society, 2024)
A large literature documenting risk factors for youth aggression, antisocial behavior, and other conduct problems has translated into a large literature outlining best-practice approaches for treating those behaviors. Yet despite general similarities in risk profiles between youth who are gang involved and those who are not, there is presently no empirically validated intervention model for helping gang-involved youth. The chapter discusses the foundations of intervention for youth aggression and related problem behaviors, along with initial efforts to extend evidence-based treatment models to gang-involved youth. It then reviews insights from developmental studies of gang-affiliated youth and young adults and connect these ideas to the intervention literature to offer a model for an effective treatment strategy for gang youth.